(3GdeYGedGJ GdGbJUGOjI ddGShGb aj GdfXGe GdGSdGejs - (3jSQj eMeO(B, (3GHh GdYdGs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2008)
(3jJVef gPG GdcJGH eGjdj (B: (3GdeYGedGJ GdJLGQjI (B: (3fXGe GdeHGOdGJ GdJLGQjI , GdMGLGJ GdYGeI , GdehGQO GdYGeI , edGeM fXGe GdShb GdESdGej GdHfGA GdGbJUGOj GdSdGej (B: (3GdWGQ GdCNdGbj ddeYGedGJ , GdGMSGf aj GdeYGedI , GdefGaSI aj GdShb GdGSdGej , GdefGaSI aj GdShb GdGSdGej , GdefGaSI GdJYGhfjI aj GdfXGe GdGSdGej VHW GdShb aj GdJTQjY GdGSdGej (B: (3eYGjjQ GdJTQjY , GdJfXje GdGSdGej ddShb , LgGR GdKef bhGYO GdQHM fXGe GdeYGedGJ GdGSdGejI (B: (3GdGUd aj GdeYGedGJ GdGHGMI , GdGSJKfGA ef GdbGYOI GdJMQje , GdGMcGe GdYGeI aj GdGMJcGQ , Mce GdGMJcGQ hCKGQgs
(3HjHdjhZQGajG U(B.181s
Keywords: (3GbJUGO GSdGejs; (3GdShbs; (3GdeYGedGJ GbJUGOjIs; (3abg ESdGejs